Role of N-methyl-d-aspartate receptor subunits GluN2A and GluN2B in auditory thalamocortical long-term potentiation in adult mice. (14th September 2021) - Zeeman, Michael; Liu, Xiuping; Zhang, Oliver; Yan, Jun
Highlights: Thalamocortical LTP was induced by tetanic stimulation of the auditory thalamus. A high ratio of GluN2A:GluN2B subunit expression favoured LTP. A low ratio of GluN2A:GluN2B subunit expression attenuated LTP. Abstract: Cortical neurons undergo continuous remodelling throughout development and into adulthood, associated with long-term changes in the synaptic transmission of thalamocortical pathways, i.e., long-term potentiation (LTP); such plasticity is input-specific, reflected in the frequency-specificity of the auditory system. It is well established that thalamocortical LTP is dependent on the activation of N-methyl-d -aspartate (NMDA) receptors. In this study, the roles of NMDA receptor subunits GluN2A and GluN2B in LTP induction were examined in thalamocortical pathways of the auditory system using subunit-selective pharmacological inhibition and in vivo tetanic stimulation of the auditory thalamus, while recording neural response in the primary auditory cortex. Long-term enhancement of thalamocortical field excitatory postsynaptic potentials (i.e., thalamocortical LTP) were induced by high frequency tetanic stimulation of the ventral division of the medial geniculate body. Such enhancement in thalamocortical fEPSPs was decreased when a GluN2A blocker (NVP-M077) was applied to the recording site in the primary auditory cortex and was increased when a GluN2B blocker (Ro25-6981) was applied. Our data suggest that the induction of thalamocortical LTP is dependent on the differential expression of the GluN2A and GluN2B subunits of NMDA receptors in thalamocortical circuits.